THE ROLE OF PHYTOMEDICATIONS IN COMPLEX THERAPY OF URINAL INFECTIONS IN CHILDREN - M.A. Mamaeva ("Paediatrician" Publishers LLC, 2008)
High prevalence of urinal infections (UI) in children, high rate of relapse and increase of antibiotic resistance force specialists to search a new complex methods of anti relapse therapy. Analysis of 380 medical cards of children showed that phytotherapy is not always used correctly; in spite of it can be important part of anti relapse therapy. The activity of different schemes of treatment of UI with phytomedicament «canephron n» included in it was studied in 110 children (aged from 5 month to 15 years). Children treated with complex therapy with antibiotics and phytomedication had no relapse in 99% of cases in 6 months and in 91% in 1 year follow up.Key words: children, urinal infections, phytotherapy.